Age-related diseases and menopausal hormone therapy – focus on progestogens - E. N. Kareva (Лечащий Врач, 2022)
Hormone therapy is the most effective treatment for menopausal symptoms. The benefits of using menopausal hormone therapy outweigh the risks for healthy women. However, the situation is more complicated in women with one or more chronic diseases. These are primarily age-associated diseases, such as hypertension, obesity, fatty liver disease, atherosclerosis, type 2 diabetes mellitus, as well as varicose veins of the lower extremities and others. Factors under hormonal control are involved in the pathogenesis of these conditions, so the use of hormone-active compounds can have both a sanogenetic effect and exacerbate the patient's morbid condition. Optimization of menopausal hormone therapy requires in-depth knowledge of the effects of hormones and their synthetic analogs on the biochemical checkpoints of age-related diseases. The pharmacological effect of menopausal hormone therapy depends not only on the dose and duration, but also on the time of onset, which translates the use of hormones from a therapeutic plane into a prophylactic one. The gestagenic component of MHT, due to additional properties, can reduce the positive metabolic effect of estrogens. A comparative analysis of the properties of progestogens showed that micronized progesterone and dydrogesterone are the safest options, with a lower risk of cardiovascular disease, thromboembolism and breast cancer compared to other progestogens, and are the drugs of choice in women with high breast tissue density, diabetes mellitus, obesity, smokers and risk factors for venous thromboembolism. Pharmacokinetic profiling shows a number of advantages of dydrogesterone: reliable quantitative accounting, the absence of biologically active metabolites (fewer side effects, including central ones), fewer contraindications for prescribing. This article presents data on the features of the use of menopausal hormone therapy in women with such chronic diseases as obesity, arterial hypertension, dyslipidemia, diabetes mellitus, venous thromboembolism.